State and Trait Anxiety and Diabetes Outcomes in Youth With Type 1 Diabetes. Issue 5 (October 2019) - Rechenberg, Kaitlyn; Szalacha, Laura; Salloum, Alison; Grey, Margaret
Purpose: The purpose of this exploratory pilot study was to examine the associations of state and trait anxiety with glycemic control, self-management, and diabetes-specific quality of life (QOL) in youth 10 to 16 years of age with type 1 diabetes (T1D). Methods: Bivariate Pearson correlations and multiple linear regression modeling were conducted to examine the relationship among anxiety symptoms, hemoglobin A1C (A1C), self-management, QOL, and covariates. Results: A sample of 67 adolescents was 50.7% female, and 87.1% were non-Hispanic white, with a mean ± SD age of 13.4 ± 1.85 years and an A1C of 8.3% ± 1.2% (67 mmol/mol). Higher state anxiety was correlated with older age. Better self-management was correlated with lower trait anxiety and lower state anxiety. Higher state and trait anxiety were associated with poorer self-management. Higher state anxiety was associated with higher A1C. Higher trait anxiety was associated with poorer diabetes-specific QOL. Conclusions: State and trait anxiety may differentially affect diabetes outcomes. State anxiety may be a modifiable target for physiologic (A1C) and psychosocial (QOL) outcomes in youth with T1D, while trait anxiety may be a modifiable target for psychosocial outcomes (QOL). Anxiety symptoms should be assessed at regular clinic visits. Interventions to improve anxiety symptoms may in turn improve physiologic and psychosocial outcomes.